Economic Effects of Reductions in Aspiration Pneumonia and Length of Hospital Stay through Introduction of Videoendoscopy - SHIBANO, Souichi; TOCHIGI, Shio; OHKUBO, Youko; NAKANE, Ayako (The Japanese Journal of Dysphagia Rehabilitation, 2011)
Nutritional care and management were established as a service at care facilities that can be charged to insurance. Oral maintenance has also been introduced as a treatment subject to the addition, given that swallowing disorders contribute significantly to malnutrition. Videoendoscopy (VE) was introduced in 2007, and the present study empirically verified the reduction in aspiration pneumonia and the economic effects of incorporating the oral maintenance plan in nutritional care and management. The phase before introduction of VE was considered Period I, and the three years after introduction were divided into Periods II–IV. For each phase, we surveyed the number of hospitalization days overall, the number of hospitalization days for aspiration pneumonia, the fall in revenue at the facility, and the addition for oral maintenance. While the length of hospitalization for aspiration pneumonia was 933 days during Period I, it fell to roughly half this during Periods II–III, and fell to roughly 190 days in Period IV. As a result, there was an overall increase in revenue of approximately ten million yen in Period IV compared to Period I. The introduction of VE and development of the oral maintenance plan led to a decrease in aspiration pneumonia, and may make it possible to ensure the QOL of users, control rising medical costs, and secure steady income for care facilities.